Gastrointestinal Stromal Tumor of the Prostate: Staging and Evaluation of Response to Therapy With 18F-FDG PET/CT. (January 2018) - Alabed, Yazan Z.
Abstract : Abstract: A 49-year-old man presented for routine general physical examination was found with an enlarged prostate gland without associated symptoms. Ultrasound followed by computed tomography (CT) of abdomen and pelvis confirmed a markedly enlarged heterogeneous prostate gland. Subsequently, a staging flourine-18 fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET/CT) scan revealed intensely FDG-avid mass involving the prostate, which was biopsied as gastrointestinal stromal tumor (GIST). The patient was treated with imatinib and a follow-up PET/CT scan showed complete metabolic response. 18 F-FDG PET/CT scan is useful in staging and follow-up of this very rare extragastrointestinal stromal tumor (EGIST).